Transitional settlement displaced populations - Corsellis, Tom; Vitale, Antonella (Oxford, 2005)
It is often the national or regional coordinators of organisations who make decisions about whether to support the building of a refugee camp or to support refugees living with host families. Technical specialists, such as physical planners, are not always available until later on in the emergency. Compared with other sectors of response, there has been very little guidance to support coordinators and specialists in making these decisions. These guidelines, developed by Shelterproject.org at the University of Cambridge, will support coordinators and specialists in responding to transitional settlement and shelter needs of displaced populations and their hosts, improving appropriateness, quality, and sustainability. They will include best-practice strategic, Programme, and project planning tools, in addition to a reference section. The book is accompanied by a free searchable CD-ROM, making this a flexible, portable, and accessible tool for fieldworkers. It will also be useful for planners and managers in Humanitarian programmes, especially those involved with shelter/protection, and also for students involved in planning, architecture and development studies courses; policy and research people in NGOs and government.
Keywords: Populations